Impact of malaria in pregnancy on infant neurodevelopment and malaria susceptibility during the first year of life in Kinshasa, the Democratic Republic of the Congo - Japhet Kabalu Tshiongo; Lise Kuseke; Thierry Kalonji; Patrick Mitashi; Aimée Mupuala; Kassoum Kayentao; Trésor Zola Matuvanga; Vivi Maketa Tevuzula; Yann Kafala; Henk D.F.H. Schallig; Hypolite Muhindo Mavoko; Petra F. Mens (International Journal of Infectious Diseases)
Objectives: To compare the neurodevelopment and malaria susceptibility of infants born to mothers infected or uninfected with malaria at the time of delivery. Methods: A cohort of 388 mother–child pairs was recruited at delivery. Maternal malaria was assessed by microscopy at birth, and infant malaria was based on a history of fever. Infant neurodevelopment was evaluated at 4-6 weeks, 6 months, and 12 months using the Mullen Scales of Early Learning (MSEL), which include scores for gross motor (GM), and early learning composite (ELC). Infant malaria incidence and neurological functioning were compared based on malaria exposure at delivery. Results: In total, 62/385 (16.1%) infants were exposed to malaria at delivery, confirmed by microscopy for both peripheral and placental malaria. These exposed infants had a significantly lower birth weight (LBW) (2824.68 ± 493.85 g) than those born of uninfected mothers (3032.69 ± 487.8 g; p = 0.0023). GM at 12 months showed no significant differences between groups (mean GM score for exposed: 47.2 ± 9.8 vs unexposed: 47.6 ± 9.7; p = 0.757). However, infants exposed to malaria infection had significantly lower ECL (−7.70 [95% confidence interval CI: −15.0, −0.36]; P = 0.04). Infant malaria, malnutrition, and LBW were significantly associated with reduced GM scores (−1.2 [95% CI: −2.25, −0.18], P = 0.021; −0.96 [95% CI: −1.92, −0.02], and −1.59 [95% CI: −3.06, −0.11], respectively). Malaria incidence peaked at 12 months, affecting 54.7% of the exposed group vs 70.6% of non-exposed infants (risk ratio = 1.04 [95% CI: 0.87-1.25], P = 0.631). Conclusions: Malaria at delivery was associated with impaired ELC but not with GM. Malaria susceptibility during the first 12 months was not influenced by maternal malaria exposure. However, LBW, malnutrition and infant malaria impacted infant development.